Perancangan Enterprise Architecture untuk Meningkatkan Indeks SPBE Pemerintah Daerah: Studi Kasus Kabupaten Tasikmalaya - Yustisiawandana, Fajri Tsani; Aji, Rizal Fathoni (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Enterprise architecture has become one of the most crucial strategic tools in the development of information technology within an organization, particularly in the public sector such as government, as it can enhance public service performance and reduce costs. In the Regional Medium-Term Development Plan (RPJMD), it was found that the assessment domain index of the National SPBE in Tasikmalaya Regency is 2.0, with the smallest value in the SPBE governance and SPBE management domains. This is partly due to the absence of enterprise architecture as a foundation or reference for implementing SPBE services in Tasikmalaya Regency. Therefore, the research adopts the methodology of the national SPBE framework or master plan as the initial reference in designing enterprise architecture, following the steps outlined in the TOGAF framework. In the business architecture, simplification is applied, reducing seven sub-activities to two new sub-activities, while addressing seven major changes to confront strategic issues. In the data architecture, five significant changes are identified as solutions to data issues in the Tasikmalaya Regency Local Government. The application architecture encompasses six significant solutions to address internal organizational issues and integrate them with the national SPBE architecture. In the technology architecture, two new technologies are added to support business, data, and application processes. In the security architecture domain, nine security additions are implemented to protect the organization from attacks on its information systems. The planning of architectural changes is structured according to the RPJMD period, spanning five years from 2026 to 2030.